Primary sinonasal mucosal melanoma simulated as cystic lesions: a case report - Shin, Sung-Ho (J Korean Assoc Oral Maxillofac Surg, 2018)
Sinonasal mucosal melanoma (SNMM) in the maxillary sinus is a rare disease condition. Compared to oral mucosal melanoma, SNMM has a bulky, exophytic, and polypoid appearance, is weakly pigmented, and associated with unspecific symptoms. Due to these features, SNMM in the maxillary sinus has been misdiagnosed as nasal polyps and chronic sinusitis. In this case report, we described SNMM occurring in the right maxillary sinus simulated as a cystic or benign lesion. Cortical bone thinning and expansion were observed around the mass. The excised soft mass was encapsulated and weakly pigmented. The mass was clearly excised and covered with a pedicled buccal fat pad graft. Diagnosis using immunohistochemistry with S-100 and homatropine methylbromide-45 (HMB-45) is critical for proper treatment.